Contos fonsequianos: um estudo sobre os modos escrita - Rios, Ana Lúcia Moreira (2018)
This work sought to understand the processes employed in the writing of Rubem Fonseca and the characteristics that maintain him in the contemporary literature. This thesis had as a problem to verify what characteristics of the contemporary narrative are present in the Fonseca's short stories, which approach or distance from the literary discussions about the genre, in order to understand how the writer manages to remain in the literary status of contemporary art. The choice by the author Rubem Fonseca was due to the thematic focus that he adopts in his contemporary production to deal with subjects that permeate the daily life of the individuals and the modes of narration, which invite the reader to participate in the events. For this study, the short stories of the writer Rubem Fonseca: Belinha and Teresa of the book She and other women (2006), contributed to the understanding of the subversion of roles on the subject villain / hero; The Cyclist, The killer of Brokers, The son and Tale of love of the book Amalgam (2013) helped to unveil the human character of the characters in the face of tragic and tales Who sees face does not see heart and Make people laugh and feel happy of Short Stories (2015), which contributed to the reflection on human miseries by focusing on the voice of the narrators, whose narratives have different characteristics in the modes of writing, constituting a true mosaic. The selected stories and the theoretical framework contributed to the identification of traits that make Rubem Fonseca's narrative and the themes adopted by the writer showed why Rubem Fonseca remains a relevant author for contemporary literature, seen as a sign of transgressiveness. In order to prove the study, the bibliographic method was used, supported by comparative analyzes that subsidized the reflections on the author's productions, as well as their literary status. The organization of the chapters contributed to the clarification of the modes of writing, as well as the positioning of the author Rubem Fonseca in the contemporary context through the analyzes in the set of works listed for this study. This thesis gave new insights to the writing process in contemporary Brazilian literary studies, destabilizing some compositional narrative conventions regarding the modes of writing, pointing to the possibility of other fictional textualities.